2019
DOI: 10.22260/isarc2019/0044
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Classification of Design Conflicts Using Rule-based Reasoning and Machine Learning—An Example of Structural Clashes Against the MEP Model

Abstract: With the emergence of 3D technologies in a recent decade, BIM software makes it easy to detect those conflicts in the early stage of a project. Clash detection in BIM software is now a common task. Among those conflicts found by BIM software, however, a relatively high percentage belongs to 'pseudo conflicts'-which are permissible or tolerable, but BIM software does not reveal this information. Thus, currently BIM managers have to manually inspect every detected conflict to classify the type of conflict. Some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…For example, if the MEP system and the structural system collide, it is considered a hard clash; in such a case, the MEP system must re-route to solve this conflict. According to [67], machine learning can be used to classify the design conflicts in BIM automatically. Furthermore, it is concluded that the current method of overlaying 2-D drawings to identify interferences of building MEP systems and structural framing is "prone to errors, causing ad-hoc rework and reduced headroom and maintainability issues" [67].…”
Section: IVmentioning
confidence: 99%
“…For example, if the MEP system and the structural system collide, it is considered a hard clash; in such a case, the MEP system must re-route to solve this conflict. According to [67], machine learning can be used to classify the design conflicts in BIM automatically. Furthermore, it is concluded that the current method of overlaying 2-D drawings to identify interferences of building MEP systems and structural framing is "prone to errors, causing ad-hoc rework and reduced headroom and maintainability issues" [67].…”
Section: IVmentioning
confidence: 99%
“…Machine Learning is a branch of computer science that focuses on imparting knowledge to the machines to self-perform tasks (Huang & Lin, 2019). The process of imparting knowledge or knowledge modeling in Machine Learning can be divided into two main steps.…”
Section: Machine Learningmentioning
confidence: 99%
“…Application of rule-based automation for clash resolution has been tested. However, developing rule-based automation systems are time-consuming, and their effectiveness depends on the number of rules defined (Huang & Lin, 2019). One alternative solution to rule-based automation is the implementation of Machine Learning.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations